Heaviness in the chest and Hodgkin Lymphoma: An unusual presentation - Sharma, Sujan; Chokhani, Ramesh; Deo, Pankaj; Chalise, Sanat (Annals of Clinical Chemistry and Laboratory Medicine, 2021)
Hodgkin lymphoma (HL) usually presents as nodal disease and may involve extranodal sites during the progression of the disease. Here we report a unusual case of Hodgkin’s lymphoma (HL) in an otherwise healthy 26 year old young male who came to the Pulmonology OPD with heaviness in the chest . An ultrasound shows mediastinal enlargement. The diagnosis of Hodgkin’s lymphoma was made on a trucut biopsy of mediastinal swelling.